Fenomena Pulau Haba Bandar dan isu alam sekitar di Bandaraya Kuala Lumpu - Shaharuddin Ahmad,; Noorazuan Md. Hashim,; Yaakob Mohd Jani, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2009)
Urban heat island (UHI) is not a new phenomenon for many of the mega cities in the world today. It is also experienced by most of the big cities in Malaysia since the last few decades . UHI can be defined as the influence of urban morphology upon natural weather and climate parameters within an urban environment.Generally, increased temperatures may be observed at urban built-up areas as compared to urban fringes and rural areas. Most researches of UHI discuss the environmental issues of urban heat island in relation to rapid urban development and industrial factors which tend to alter natural patterns and trends of temperatures within the urban environment. This study analyses some of these aspects of the UHI patterns in Kuala Lumpur in recent years by using remote sensing, TM landsat satellite imaging and ETM+ as well as GIS techniques to detect any temperature pattern changes in Kuala Lumpur, and in accordance with different landuse sectors. The results demonstrate that there were many areas that had recorded medium high temperatures such as Jinjang-Kepong, Segambut-Sentul and a few other locations at the south of the study area since UHI patterns were detected there. As an urban environmental issue the UHI phenomenon was closely related to aspects of conservation and preservation of the urban environment, which in turn denoted the fact that beside physical factors, human factors were also important in determining the nature of the UHI intensity in the Kuala Lumpur city